2015
DOI: 10.1002/app.41844
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl functionalized PVDF–TiO2 ultrafiltration membrane and its antifouling properties

Abstract: In this study, polyvinylidene fluoride (PVDF) was hydroxylized via the Fenton reaction and was used as a polymer matrix for mixed‐matrix membrane synthesis. The chemical properties of hydroxylized PVDF (PVDF–OH) polymer and pristine PVDF polymer were investigated by Fourier transform infrared spectroscopy (FTIR). Treatment of PVDF polymer with Fenton reagent led to the emergence of the OH functionality. The field emission scanning electron microscope (FESEM) and energy dispersive X‐ray (EDX) analysis clearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Membrane technology has acquired greater interest in nanomaterials for the development of mixed‐matrix membranes (MMMs). Hybrids of nanomaterials and organic polymers are referred to as MMMs . This combination finds various applications in membrane processes such as gas separation, pervaporation, and liquid separation .…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology has acquired greater interest in nanomaterials for the development of mixed‐matrix membranes (MMMs). Hybrids of nanomaterials and organic polymers are referred to as MMMs . This combination finds various applications in membrane processes such as gas separation, pervaporation, and liquid separation .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the doping of hydrophilic nanoparticles in hydrophobic polymers, such as PSf, makes the membranes more hydrophilic and, thus, provides fouling resistance against proteins and other foulants that are hydrophobic in nature . Therefore, various nanoparticles have been incorporated into polymer structures to mitigate membrane fouling; these include nanosilver, nano titanium dioxide (TiO 2 ), nano zinc oxide (ZnO), nanoalumina (Al 2 O 3 ), graphene, and carbon nanotubes (CNTs) . Although these nanocomposite membranes could provide new dimensions for next‐generation membranes with better antifouling properties, there are still challenges, including the fact that the nonhomogeneous dispersion of nanomaterials in the polymer matrix causes a deterioration in the membrane properties because of agglomerated nanoparticles caused by a high surface energy…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology has created much interest in nanomaterials for the expansion of mixed matrix membranes (MMMs). 13 Hybrids of hydrophilic nanoparticles with a membrane www.soci.org V Vatanpour et al lead to fouling decreases and could resolve the major problem of filtration membranes. 14 Polymeric materials used in the manufacture of membranes, such as polyethersulfone (PES), polyvinylidene fluoride (PVDF) and polysulfone (PSf ), are usually hydrophobic and hydrophilic nanoparticles could improve their hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%